The abbreviated form of the Brief Cognitive Battery in the diagnosis of dementia in Alzheimer's disease - Stephanie Castro; Antonio Eduardo Damin; Cláudia Sellitto Porto; Paulo Caramelli; Ricardo Nitrini (Dementia & Neuropsychologia)
Abstract The Brief Cognitive Battery (BCB) developed by our group for cognitive assessment of low educated individuals has also shown to be highly accurate in diagnosing dementia of individuals with medium or high levels of education, making it a useful tool for populations with heterogeneous educational background. The application of BCB takes around eight minutes, a rather long period for a screening test. Objectives: Our aim was to evaluate whether the exclusion of items of the BCB could reduce its application time without losing accuracy. Methods: Patients with Alzheimer's disease with mild or moderate dementia (N=20), and 30 control subjects were submitted to an abbreviated version of the BCB in which the clock drawing test was not included as an interference test for the delayed recall test. Data from another 22 control individuals who were submitted to the original BCB in another study were also included for comparison. A mathematical formula was employed to compare the two versions of the BCB. Descriptive statistics and ROC (receiver operator characteristic) curves were used (alpha=0.05). Results: Using the abbreviated version, the delayed recall test also had high accuracy in diagnosing dementia and the mathematical formula results did not differ to those obtained using the original version, while mean time was reduced by 2 minutes and 37 seconds. Conclusions: This abbreviated form of the BCB is a potentially valuable tool for screening dementia in population studies as well as in busy clinical practices in countries with heterogeneous educational backgrounds.